The Four Noble Truths and International Dispute Settlement - Jittapanyo (Poonok), Phramaha Suttidon (Journal of Modern Learning Development, 2023)
As the world is facing conflicts and violence that have caused problems and obstacles to peaceful human co-existence for ages, many have concluded that conflict and violence are human nature due to their common occurrence in human history. When conflicts are resolved, peaceful co-existence is possible, otherwise, conflict will become direct and indirect violence. Solving conflicts with violence only lead to massive life and property loss, reflecting how co-existence would be without peace, and such violence and conflict only grow more complex and subtle. The author therefore used conflict in Aceh, Republic of Indonesia, for analysis to show the Alternative Dispute Resolution : ADR through non-state actors according to the concept of neo-liberalism and integration with The Four Noble Truths, with the goal to release conflicting parties from the violence trap through the Eight Noble Paths, as one way to reconcile conflict.